Selective coherent phonon-mode generation in single-wall carbon nanotubes. (12th December 2016) - Nugraha, Ahmad R T; Hasdeo, Eddwi H; Saito, Riichiro
Abstract: The pulse-train technique within ultrafast pump-probe spectroscopy is theoretically investigated to excite a specific coherent phonon mode while suppressing the other phonon modes generated in single-wall carbon nanotubes (SWNTs). In particular, we focus on the selectivity of the radial breathing mode (RBM) and the G-band for a given SWNT. We find that if the repetition period of the pulse train matches with the integer multiple of the RBM phonon period, the RBM amplitude can be maintained while the amplitudes of the other modes are suppressed. As for the G-band, when we apply a repetition period of a half-integer multiple of the RBM period, the RBM can be suppressed because of destructive interference, while the G-band still survives. It is also possible to keep the G-band and suppress the RBM by applying a repetition period that matches with the integer multiple of the G-band phonon period. However, in this case we have to use a large number of laser pulses having a property of "magic ratio" of the G-band and RBM periods.